2011
DOI: 10.1109/jstqe.2011.2134075
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Resolved Nonlinear Dynamics Induced by Orthogonal Optical Injection in Long-Wavelength VCSELs

Abstract: We report a first experimental study of the polarization-resolved nonlinear dynamics of a 1550 nm singlemode VCSEL subject to orthogonal optical injection. Stability maps identifying the boundaries between regions of different nonlinear dynamics are reported for two different values of the bias current. A rich variety of nonlinear behaviours including periodic, period doubling, and irregular dynamics are observed for both polarizations. Polarization switching and injection locking induced by the optical inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…These include single-longitudinal mode operation, circular beam profile, reduced fabrication costs, ease of fabrication of two-dimensional arrays, etc. Studies of nonlinear dynamics of optically injected semiconductor lasers have been extended to VCSELs [6][7][8][9][10][11][12][13][14][15] since these devices offer additional degrees of freedom, like the presence of multiple transverse modes and the direction of the emitted polarization, when compared with their edge-emitting counterparts. The behavior of these systems not only includes the previously mentioned dynamical regimes but also polarization switching (PS) and optical bistability [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include single-longitudinal mode operation, circular beam profile, reduced fabrication costs, ease of fabrication of two-dimensional arrays, etc. Studies of nonlinear dynamics of optically injected semiconductor lasers have been extended to VCSELs [6][7][8][9][10][11][12][13][14][15] since these devices offer additional degrees of freedom, like the presence of multiple transverse modes and the direction of the emitted polarization, when compared with their edge-emitting counterparts. The behavior of these systems not only includes the previously mentioned dynamical regimes but also polarization switching (PS) and optical bistability [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The specific injection scheme with orthogonally polarized master and slave lasers produces new features, like PS, that cannot be found when dealing with parallel optical injection. Nonlinear dynamics of VCSELs under orthogonal optical injection has been experimentally and theoretically analyzed for 850 [7][8][9][10][11][12] and 1550 nm [13][14][15] wavelength devices. Rich nonlinear dynamics, including period doubling, quasiperiodicity, injection locking, bistability, and chaos, have been found in short-wavelength VCSELs [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 4 can be explained from the effects induced by polarised optical injection. 19,21,22 Fig. 3 shows the case where PS appears associated with injection locking 19 (this is a situation in which the orthogonal polarization mode of the VCSEL locks to the injected field and has constant output intensity with emission at the wavelength of the external signal 15 ).…”
mentioning
confidence: 99%
“…4(b), the parallel polarization is significantly attenuated but not completely suppressed. 19,21,22 In such cases, it has been demonstrated that the two polarized outputs of the VCSEL can both exhibit limit cycle dynamics. 21,22 This is the case here where an attenuated periodic signal is also obtained in the parallel polarization, showing a similar behaviour to the sub-threshold oscillations of biological neurons.…”
mentioning
confidence: 99%